Dekonstruksi Independensi KPK Pasca-Revisi UU No. 19 Tahun 2019: Analisis Politik Hukum dan Penanganan Korupsi Pejabat Eksekutif - NOVI ENJELINA PUTRI; Muhaimin (Jurnal Politik Pemerintahan Dharma Praja, 2025)
The revision of the Corruption Eradication Commission Law through Law No. 19 of 2019 has sparked serious debate regarding the weakening of the institution and the erosion of the KPK's independence, particularly in handling corruption cases involving executive officials. This article aims to analyze how the KPK's independence has been reconstructed after the revision and how this is reflected in law enforcement practices. The analysis was conducted on a number of strategic decisions, including the cases of Edhy Prabowo, Juliari Batubara, Syahrul Yasin Limpo, and Lukas Enembe, which show indications of structural and procedural weakening, as well as inconsistencies in the judicial and criminal justice processes. A comparison is made with the Independent Commission Against Corruption (ICAC) model in Hong Kong, which has proven highly effective thanks to guaranteed institutional independence, operational transparency, and active community involvement in corruption prevention. The results of the study show that after the revision, the independence of the KPK has experienced a shift in the political direction of law enforcement in combating corruption in Indonesia, structural weaknesses reflected in procedural interventions, changes in investigation patterns, and inconsistencies in verdicts against high-level corruption perpetrators, as well as a spirit of independence that is vulnerable to political intervention. This article recommends reinforcing the legal framework that guarantees the KPK's operational independence and conducting a systemic evaluation of political influence in